2002
DOI: 10.1161/01.cir.0000035037.11968.5c
|View full text |Cite
|
Sign up to set email alerts
|

Systolic Improvement and Mechanical Resynchronization Does Not Require Electrical Synchrony in the Dilated Failing Heart With Left Bundle-Branch Block

Abstract: Background-Biventricular (BiV) and left ventricular (LV) pacing similarly augment systolic function in left bundlebranch block (LBBB)-failing hearts despite different electrical activation. We tested whether electrical synchrony is required to achieve mechanical synchronization and functional benefit from pacing. Methods and Results-Epicardial mapping, tagged MRI, and hemodynamics were obtained in dogs with LBBB-failing hearts during right atrial, LV, and BiV stimulation. BiV and LV both significantly improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
310
0
4

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 430 publications
(332 citation statements)
references
References 20 publications
18
310
0
4
Order By: Relevance
“…10 Fusion with electrical activity from the AV node is a possibility [11][12][13] ; however, experimental data have suggested that electrical synchrony is not a prerequisite for mechanical synchrony. 14 Another possible explanation is that early activation of the lateral wall is preferable to the septum, ie, that dyssynchrony associated with right bundle-branch block-type delay is less than that associated with left bundle-branch block-type delay. 10 This is consistent with regional motion analysis of left versus right bundle-branch block, where initial prestretch of the opposing wall is greater with early septal activation.…”
Section: Discussionmentioning
confidence: 99%
“…10 Fusion with electrical activity from the AV node is a possibility [11][12][13] ; however, experimental data have suggested that electrical synchrony is not a prerequisite for mechanical synchrony. 14 Another possible explanation is that early activation of the lateral wall is preferable to the septum, ie, that dyssynchrony associated with right bundle-branch block-type delay is less than that associated with left bundle-branch block-type delay. 10 This is consistent with regional motion analysis of left versus right bundle-branch block, where initial prestretch of the opposing wall is greater with early septal activation.…”
Section: Discussionmentioning
confidence: 99%
“…MR 3D tagged images were obtained (GE Signa 1.5T) during either RA or RV free-wall stimulation, and mechanical dyssynchrony indexed by a circumferential uniformity ratio estimate (CURE), as described previously. 9 Perfectly synchronous or dyssynchronous contraction patterns yield CURE indices of 1 or 0, respectively.…”
Section: Assessment Of Mechanical Dyssynchronymentioning
confidence: 99%
“…Electrical dyssynchrony may not adequately describe the degree of mechanical dyssynchrony present; and therefore, the QRS duration may not be the best predictor of patient response to CRT [10][11][12]. Efforts have been made to improve the selection of patients who might benefit from CRT by using imaging modalities to define cardiac dyssynchrony more precisely.…”
Section: Introductionmentioning
confidence: 99%